A New No-Equilibrium Chaotic System and Its Topological Horseshoe Chaos - Chunmei Wang; Chunhua Hu; Jingwei Han; Shijian Cang (Advances in Mathematical Physics)
A new no-equilibrium chaotic system is reported in this paper. Numerical simulation techniques, including phase portraits and Lyapunov exponents, are used to investigate its basic dynamical behavior. To confirm the chaotic behavior of this system, the existence of topological horseshoe is proven via the Poincaré map and topological horseshoe theory.